Hemorrhagic events in hepatocellular carcinoma patients treated with antiangiogenic therapies. Issue 3 (18th January 2013) - Duffy, Austin; Wilkerson, Julia; Greten, Tim F.
Abstract: The presence of cirrhosis increases the potential risk of hemorrhage for patients with hepatocellular carcinoma (HCC). We evaluated the relative risk for hemorrhage in patients with HCC treated with antiangiogenic agents. We performed a systematic review and meta‐analysis of antiangiogenic studies in HCC from 1995 to 2011. For nonrandomized studies we compared bleeding risk with other HCC single‐arm studies that did not include an antiangiogenic agent. To separate disease‐specific factors we also performed a comparison analysis with renal cell cancer (RCC)) studies that evaluated sorafenib. Sorafenib was associated with increased bleeding risk compared to control for all grade bleeding events (odds ratio [OR] 1.77; 95% confidence interval [CI] 1.04, 3.0) but not grade 3‐5 events in both HCC and RCC (OR 1.46; 95% CI 0.9, 2.36; P = 0.45). When comparing the risk of bleeding in single‐arm phase 2 studies evaluating antiangiogenic agents, this risk for all events (OR 4.34; 95% CI 2.16, 8.73) was increased compared to control. Conclusion: This analysis of both randomized and nonrandomized studies evaluating an antiangiogenic agent in HCC showed that whereas the use of sorafenib was associated with an increased risk of bleeding in HCC, this was primarily for lower‐grade events and similar in magnitude to the risk encountered in RCC. (HEPATOLOGY 2013)